WEBVTT
00:00:01.110 --> 00:00:08.110
Simplify the expression six π₯ plus two π¦ minus three π₯ minus four π¦.
00:00:09.040 --> 00:00:13.370
In order to simplify this expression, we need to group the like terms.
00:00:13.590 --> 00:00:15.810
Letβs look at the π₯ terms first.
00:00:16.250 --> 00:00:19.480
We have six π₯ minus three π₯.
00:00:20.410 --> 00:00:26.060
This gives us three π₯, as six π₯ minus three π₯ is equal to three π₯.
00:00:27.200 --> 00:00:30.370
We also need to group or collect the π¦ terms.
00:00:30.580 --> 00:00:34.110
We have a positive two π¦ and a negative four π¦.
00:00:35.110 --> 00:00:40.560
Grouping these, two π¦ minus four π¦ gives us negative two π¦.
00:00:41.910 --> 00:00:52.480
Therefore, the simplified version of the expression six π₯ plus two π¦ minus three π₯ minus four π¦ is three π₯ minus two π¦.